PENGARUH KESADARAN WAJIB PAJAK, PELAYANAN FISKUS DAN TAX AMNESTY TERHADAP KEPATUHAN WAJIB PAJAK NON-KARYAWAN (Wajib Pajak Orang Pribadi yang Terdaftar di Kantor Pelayanan Pajak Pratama Malang Selatan) - Desy Purnamasari; Jeni Susyanti; M. Agus Salim (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACKThe purpose of this study is to examine: 1) The influence of the taxpayers' awareness of individual taxpayer compliance. 2) The influence of the service of tax authorities on taxpayer compliance of individual taxpayers. 3) The influence of tax amnesty on individual taxpayer compliance. This research is descriptive research with quantitative approach with primary data. The population of this study is individual taxpayers of non-employee which are registered in tax service office Pratama Malang Selatan. Determination of the sample is done by incidental sampling method, with total of respondents of 100 taxpayers and method of data collection using questionnaires.Based on the results of the analysis, it can be seen that : 1) Taxpayer awareness has a significant positive impact on non-employee taxpayer compliance. 2) Fiscal services have a significant positive impact on non-employee taxpayer compliance. 3) Tax amnesty has a significant positive impact on non-employee taxpayer compliance. Keywords: Tax compliance, The taxpayer awareness, The service tax authorities and Tax Amnesty and Non-Employee Individual Taxpayers.